Diskursus Konsep Jiwa dan Ketuhanan: Studi Komparasi Pemikiran Aristoteles dan Al-Kindi - Muhammad Dwi Novanto (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
The thought discourse that the author means here is about ideas verbally and expressing his thoughts formally and regularly from the two figures, Aristotle and Al-Kindi. Aristotle himself was an early figure during the Peripatetic tradition whose learning method used logic and was carried out at a leisurely pace. Meanwhile, the philosopher Al-Kindi is a philosopher who is nicknamed the father of Islamic philosophy, because with his discipline, Al-Kindi has studied Islamic philosophical issues specifically and seriously. Apart from that, Al-kindi was the first philosopher who was able to combine religion and philosophy, as well as revelation and reason. This qualitative research aims to analyze more deeply the similarities and differences in the thoughts of Aristotle and Al-Kindi. Meanwhile, the results of this research reveal that there are differences in thoughts and similarities regarding the concepts of Soul and Divinity, one of which is that the Soul according to al-Kindi is eternal and impermanent according to Aristotle. The author found a discussion that was unique to the two philosophers regarding the soul and divinity. The method used in this research is a qualitative descriptive method with analysis that utilizes data and collects data from various sources and then explains it descriptively.